2017
DOI: 10.1177/2058460117700449
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and locations of systemic metastases in Merkel cell carcinoma by imaging

Abstract: BackgroundThe primary neuroendocrine skin cancer, Merkel cell carcinoma (MCC), has a well-known predilection to metastasize systemically. However, the experience of systemic metastases in MCC is mainly disseminated through case reports due to the rarity of MCC.PurposeTo elucidate the frequency and locations of systemic metastasis in MCC by reviewing the imaging of patients with metastatic MCC in a national cohort.Material and MethodsPatients with diagnosed metastatic MCC by imaging studies in Finland during 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 30 publications
3
46
0
4
Order By: Relevance
“…33 Distant LNs and intra-abdominal organs were most often the first sites of distant metastases in the present study, consistent with previous findings that these sites are frequently involved in metastatic MCC. 12,13,34 While we found that the lung (0%) and brain (3%) were rarely the first sites of distant spread, they may be subsequently involved in 30% and 13% of patients, respectively. 34 Understanding these patterns of metastasis may help to guide follow-up imaging strategies.…”
Section: Discussionmentioning
confidence: 62%
“…33 Distant LNs and intra-abdominal organs were most often the first sites of distant metastases in the present study, consistent with previous findings that these sites are frequently involved in metastatic MCC. 12,13,34 While we found that the lung (0%) and brain (3%) were rarely the first sites of distant spread, they may be subsequently involved in 30% and 13% of patients, respectively. 34 Understanding these patterns of metastasis may help to guide follow-up imaging strategies.…”
Section: Discussionmentioning
confidence: 62%
“…Liver is one of the most important solid organs for MCC metastization, typically in the form of a nodular lesion, well-defined on imaging examinations [6]. In this case, the metastization occurred in a diffuse pattern, with less representation in the imaging techniques, which is another interesting and rare finding that supports the performance of liver biopsy.…”
Section: Discussionmentioning
confidence: 68%
“…MCC is a highly metastatic cancer involving all organs, which contributes to its high morbidity and mortality 12 . Once seeded, micro-metastases must grow and establish a tumor.…”
Section: Mainmentioning
confidence: 99%